Separation of micro-phytoplankton from inorganic particulate in Antarctic seawater (Ross Sea) for the determination of Cd, Pb and Cu: optimization of the analytical methodology. Issue 13 (9th June 2015) - Truzzi, C.; Annibaldi, A.; Finale, C.; Libani, G.; Romagnoli, T.; Scarponi, G.; Illuminati, S.
Abstract : Phytoplankton vs. inorganic particulate in Antarctic seawater: which gives major contribution to the heavy metal content? A new method to discover it. Abstract : The aim of this work was the optimization and validation of an analytical methodology for the determination of Cd, Pb and Cu in Antarctic phytoplankton that provide the physical separation of algal components from inorganic particulate, followed by the microwave digestion to make the sample suitable for voltammetric analysis. The physical separation of phytoplankton from non-algal particulate, referring to a method of Utermöhl, proved to be an accurate method for the separation of micro-phytoplankton larger than 2 μm. The fraction in mass of micro-phytoplankton relating to the whole particulate phase can vary considerably (from 7% to 100%) depending on the sampling period (presence/absence of algal cells) and on the depth. This result shows that the separation of algal particulate from the inorganic one is necessary to know the distribution of heavy metals inside the particulate phase. The method of choice for the microwave digestion of phytoplankton cells is the mineralization with HCl and H2 O2 . Compared to the digestion with HNO3 and HF, it permits the determination of Cd, Pb and Cu by square wave anodic stripping voltammetry without successive extreme dilution of the sample, reducing the time of analysis and improving accuracy and precision of the analytical technique. First preliminary data on heavy metal concentration in micro-phytoplankton of Antarctic seawater (Ross Sea) are: Cd, ∼0.30 μg g −1 dw (dry weight), Pb, 0.13–0.24 μg g −1 dw, and Cu, 1.2–1.7 μg g −1 dw.